2014
DOI: 10.1039/c4ra12877j
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study on the effect of a surface protecting agent on electrocrystallization of silver nanoparticles

Abstract: Cyclic voltammetry and chronoamperometry at characteristic potentials were employed to unravel the mechanism of electrocrystallization of silver nanoparticles (AgNPs) from their aqueous solution in the presence and absence of surface protecting agent tetrabutylammonium tetrafluoroborate (TBABF 4 ). The electrocrystallization parameters viz. initial current density (j 0 ), decay constant (s), diffusion coefficient (D) of Ag(I), number of active sites (N 0 ) and nucleation rate (a) were calculated by fitting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…[31,32] The work function, Y,c an be expressed by an empirical equation dependento nDE p [Eq. (14)]. Under this condition, the formal redox potential( E 0 ')a nd the standard heterogeneous rate constant (k 0 )o ft he redox reaction can be obtained by Equations (15) and (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,32] The work function, Y,c an be expressed by an empirical equation dependento nDE p [Eq. (14)]. Under this condition, the formal redox potential( E 0 ')a nd the standard heterogeneous rate constant (k 0 )o ft he redox reaction can be obtained by Equations (15) and (16).…”
Section: Resultsmentioning
confidence: 99%
“…[12] In this respect, severalt emplate-free electrosynthesis strategies have been developedinrecent years for the controlled electrochemicals ynthesis of metal nanoparticles on conventional electrode materials. [13][14][15][16][17][18][19][20][21][22] However,t ot he best of our knowledge, no attempt has been made to investigate the templateand additive-freee lectrosynthesis of gold nanoparticleso n ah ydrophobic, soft substrate such as C-PDMS, whichi sp resented here from an aqueous solution of HAuCl 4 in dilute hydrochlorica cid (HCl). Any chemical or physical treatment of C-PDMS and addition of further chemicals have been avoided during the electrochemical preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, it has been found that J ST , N ðtÞ, and N 0 obtained experimentally from surface analysis (J ST ÀEXP , N ðtÞ EXP , and N 0ÀEXP ) may be several orders of magnitude higher than those obtained from the CTTs (J ST ÀCTT , N ðtÞ CTT , and N 0ÀCTT ) [19,21,28,41,46,47]. Therefore, some important clarifications related to the interpretation of these data are needed.…”
Section: Recent Advances In Analytical and Numerical Modeling Of Elecmentioning
confidence: 99%
“…Electrosynthesis is a room-temperature solution phase route to prepare supported metal nanoparticles on electrodes by transferring electrons from external source to the metal ion precursor present in the solution. Although this process can produce metal nanoparticles of best possible chemical purity, the control of size and shape of nanoparticles is very challenging task as it depends on several parameters such as strategy of electrochemical synthesis [5,6], potential pulse parameters [7], nature of the substrate materials [8], and presence of any additional chemical reagents [9]. Different strategies had been adapted to date to prepare platinum nanoparticles of different sizes and shapes by employing cyclic voltammetry at constant scan rate [10] and potentiostatic pulses [11][12][13].…”
Section: Introductionmentioning
confidence: 99%